Teachers’ Attitudes Towards Inclusion of Learners with Disabilities at American Private Early Childhood Education in Dubai: An Investigative Study - Fakih, Mirna (2019)
Inclusion has been defined as an international phenomenon that emphasizes the need to provide Special educational services to learners with Disabilities known as (people of determination in Dubai) within the mainstream classrooms. The effectiveness of “inclusion” is considered as a common belief among researchers and educator’s dependent on teachers’ roles and attitudes that was evident in various tentative studies over the last decade. Therefore, to be able to create a less restricted environment in classrooms, both general and special educators’ attitudes are considered the main agents for such phenomenon. As such, the researcher aimed in this study to highlight the main challenges facing kindergarten mainstream teachers in three American private schools in Dubai (UAE). These stem from the recent educational reforms towards inclusion by scrutinizing Kindergarten teachers ‘attitudes towards including children with disabilities, their readiness and capability to accommodate children in mainstream classrooms, perceptions towards the issues of inclusive education, and their attitudes towards the admission and provision offered to such students. The study includes a range of literature reviews that highlights best practices of inclusion and teachers’ attitudes around the world and is designed to rely on a mixed methods-approach. This is done by conducting a survey-questionnaire that was given to regular kindergarten teachers working in three private schools in Dubai, in addition to semi-structured interviews with teachers, and observations of SEND students in mainstream classrooms. An analysis of data collected from three schools indicated that kindergarten teachers held positive attitudes towards inclusion and viewed it is a beneficial practice for all learners in regular classrooms, while others showed negative and neutral attitudes. Hence, the results indicated that successful inclusion relies on important variables such as training, support from administrators and stakeholders to access services, resources and provisions in order to generate positive attitudes to meet their SEND students in the mainstream education setting. This study ended with further research-based recommendations for future practice in inclusive education by overcoming barriers and challenges to inclusion that negatively influence teachers’ attitudes amongst kindergarten teachers at governmental schools.